Triple therapy approach for treating chromoblastomycosis in a Lebanese patient - Joe Khodeir; Paul Ohanian; Hala Abi Rached Megarbane (Clinical Case Reports)
Key Clinical Message Chromoblastomycosis, though rare in non‐endemic regions like Lebanon, should be considered in patients presenting with chronic, verrucous skin lesions unresponsive to conventional therapies. Multimodal treatment combining oral antifungals, cryotherapy, and adjunctive topical 5‐Fluorouracil demonstrates efficacy in managing refractory cases. Follow‐up visits three and 6 months after treatment cessation showed sustained lesion clearance and no recurrence.